HUBUNGAN KECERDASAN EMOSIONAL DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA SDN DI KECAMATAN PANAKKUKANG KOTA MAKASSAR - Ulfayani Hakim; Nurhikmah H; Umar Tirtaraharja (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2023)
This research aimed at: (1) describing student’s emotional quotion, learning motivation, and learning achievement, (2) find out the correlation of student’s emotional quotion and learning achievement, (3) find out the correlation of student’s learning motivation and learning achievement, and (4) find out the correlation between student’s emotional quotion and learning motivation to learning achievement. This type of research is ex post facto with correlational. The population in the study were all student of elementary school at Panakkukang District Makassar City. The sample in the study are 150 student from 3 elementary school that choosen by multistage sampling. The data obtained from samples were analyzed by simple correlation and multiple regression. The result shows: (1) student’s emotional quotion, learning motivation, and learning achievement are in good category, (2) there is a correlation of emotional quotion and learning achievement on Student in State Elementary School at Panakkukang District Makassar City, (3) there is a correlation of learning motivation and learning achievement on Student in State Elementary School at Panakkukang District Makassar City, (4) there is a correlation between emotional quotion and learning motivation to learning achievement on Student in State Elementary School at Panakkukang District Makassar City. The conclusion from the results of this study is that there is a relationship between emotional intelligence and learning motivation with the learning achievement of SDN students in Panakkukang District, Makassar City.